The Circadian Clock in Lepidoptera - Brady, Daniel; Saviane, Alessio; Cappellozza, Silvia; Sandrelli, Federica (Frontiers in Physiology, 2021)
With approximately 160,000 identified species of butterflies and moths, Lepidoptera are among the most species-rich and diverse insect orders. Lepidopteran insects have fundamental ecosystem functions as pollinators and valuable food sources for countless animals. Furthermore, Lepidoptera have a significant impact on the economy and global food security because many species in their larval stage are harmful pests of staple food crops. Moreover, domesticated species such as the silkworm Bombyx mori produce silk and silk byproducts that are utilized by the luxury textile, biomedical and cosmetics sectors. Several Lepidoptera have been fundamental as model organisms for basic biological research, from formal genetics to evolutionary studies. Regarding chronobiology, in the 1970s Truman's seminal transplantation experiments on different lepidopteran species were the first to show that the circadian clock resides in the brain. With the implementation of molecular genetics, subsequent studies identified key differences in core components of the molecular circadian clock of Lepidoptera compared to the dipteran Drosophila melanogaster, the dominant insect species in chronobiological research. More recently, studies on the butterfly Danaus plexippus have been fundamental in characterizing the interplay between the circadian clock and navigation during the seasonal migration of this species. Moreover, the advent of Next Generation Omic technologies has resulted in the production of many publicly available datasets regarding circadian clocks in pest and beneficial Lepidoptera. This review presents an updated overview of the molecular and anatomical organization of the circadian clock in Lepidoptera. We report different behavioral circadian rhythms currently identified, focusing on the importance of the circadian clock in controlling developmental, mating and migration phenotypes. We then describe the ecological importance of circadian clocks detailing the complex interplay between the feeding behavior of these organisms and plants. Finally, we discuss how the characterization of these features could be useful in both pest control, and in optimizing rearing of beneficial Lepidoptera.